Isolation and Identification of Serum Gamma Immunoglobulin (IgG) of Native and Imported Chickens By Ion Exchange Chromatography and Immunochernistry Methods - Murniaty Simorangkir; Aisjah Girindra; Fachriyan H. Pasaribu; Wasmen Manalu (Forum Pasca Sarjana, 1995)
The study was designed to isolate and identify serum IgG of native and imported chickens, after being immunized with Newcastle Disease Vaccine. The isolation method used was the DEAE-Cellulose ion exchange chromatography using 0.01 M Tris-HCl buffer, at pH 8.0, with linear gradient NaCl from 0.01 M to 0.30 M after salting out with anhydrous Na2SO4. Identification of IgG characteristics carried out using the Ouchterlony double immunodiffusion, immuno-electrophoresis and SDS-PAGE 8% methods. Serum fractionation of native and imported chickens using the DEAE-Cellulose chromatography, after salting out with anhydrous Na2So4 of 18,14 and 14% resulted in four peaks of protein fractions.